Coconut Estate - (:unkn) unknown (My University, 2009)
A picture looking through the tall coconut trees on an estate.
Colour: Black and White; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Coconut palm--Trinidad and Tobago; Coconut industry--Trinidad and Tobago; Agriculture--Trinidad and Tobago